Skrining Awal Kesehatan Santriwati dan Pemberian Tablet Tambah Darah untuk Mencegah Stunting - Winarningsih, Wiwik (Journal of Dedicators Community, 2024)
Anemia for young women will be at risk of giving birth to unhealthy babies,premature birth, low birth weight and stunting. The prevalence of anemia inPP Putri Wahid Hasym Bangil is still quite high. The results of social serviceactivities in 2018 showed that the anemia rate among female students was46%. This figure is higher than the prevalence of anemia in teenagers inIndonesia, which is 32%. The method of empowering this communitypartnership is the formation of a cadre of WITNESSES BERI TTD; Cadretraining and counseling to all female students; Hb examination and initialhealth screening of students; Giving TTD; Assistance with drinking TTDand monitoring and evaluation. Results and Discussion: The pretest resultsobtained by the female students were 38.6%, after counseling and training,the posttest results showed that 95.7% of the female students had a very goodlevel of understanding. These results prove that this activity is able to providematerial supplies for female students who will later be confirmed as SAKSIBERI TTD cadres. In conclusion, this activity has a positive impact and newenthusiasm for female students so they can meet their nutritional needs everyday so as to avoid anemia and stunting. Students who are diagnosed withanemia will then receive assistance in consuming blood supplement tablets.